Determining prey spectra of carnivorous sundews using DNA-metabarcoding - Krueger, Thilo Alexander (Curtin University, 2021)
Prey spectra of five closely-related species of carnivorous plants (Drosera sect. Arachnopus, Droseraceae) were investigated in their natural habitats in Western Australia using novel in-situ macro photography and DNA-metabarcoding techniques. Accurate analysis of prey spectra (even of heavily digested prey) at a taxonomic resolution and level of completeness unachievable by morphology-based methods was demonstrated. Observed prey selectivity in the scented D. fragrans supported the existence of an olfactory prey attraction strategy in this species.